CHANGES IN MARKERS OF ENDOTHELIAL FUNCTION, LIPID PEROXIDATION AND ANTIOXIDANT PROTECTION IN PREGNANT WOMEN WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - О. Олексяк; C. Геряк (Bukovynian State Medical University, 2022)
Introduction. Increasing prevalence of chronic obstructive pulmonary diseases (COPD) in the female population requires timely diagnosis of COPD in pregnant women. Changes in markers of lipid peroxidation and antioxidant protection, which eventually lead to endothelial dysfunction, play a prominent role in pathophysiology of COPD disorders. During pregnancy, these changes cause obstetric and perinatal complications. The aim of our study was to determine the effect of markers of endothelial dysfunction, lipid peroxidation and antioxidant protection on the development of obstetric and perinatal complications in pregnant women with chronic obstructive pulmonary disease of different severity. Materials and methods. Fifty-six pregnant women with clinically and instrumentally verified signs of COPD were examined. The main group of pregnant women was divided into the IA subgroup (29 women with mild bronchial obstruction) and the IB subgroup (27 women with moderate bronchial obstruction). The control group consisted of 24 healthy pregnant women. The function of biochemical markers of endothelial function (endothelin-1 and circulating desquamated endotheliocytes) and the activity of lipid peroxidation and antioxidant protection (malondialdehyde, diene conjugates, superoxide dismutase) were assessed in all groups of women. The incidence of obstetric and perinatal complications in the examined groups of pregnant women with COPD was determined. Results and discussion. In pregnant women with signs of COPD there was a pronounced tendency for the levels of intermediate products of lipid peroxidation to increase (malondialdehyde was 22.6% higher in the IA subgroup and 52.9% higher in the IB subgroup, The study group showed a marked tendency toward an increase in the levels of lipid peroxidation intermediates (malondialdehyde increased in the IA and IS subgroups by 22.6% and 21.9%, respectively, compared with controls) and a decrease in the enzymatic activity of the antioxidant protection system (superoxide dismutase decreased by 15.9% and 21.2% in the IA and IB subgroups, respectively, compared with controls). As a result of the imbalance in the LPO/AOP system and the development of endothelial dysfunction, we observed an increase in the development of obstetric and perinatal complications in pregnant women of the main group who had COPD. Anemia (41.4% in the IA and 63.2% in the IB subgroup), placental dysfunction (51.7% in the IA and 66.6% in the IB subgroup), preterm birth threat (13.8% and 25.9%, respectively), and fetal growth retardation syndrome (13.8% and 22.2%, respectively) were more common. Conclusions. Pregnant women with COPD have abnormalities in basic markers of endothelial function, lipid peroxidation and antioxidant protection, which are accompanied by an increased incidence of obstetric and perinatal complications and require the development of adequate treatment and prophylaxis programs in pregnant women with COPD.